A study of language use on public signage, billboards and commercial advertisements in Pakistan - Maryam Maheen Moon; Nida Kainat; Shehzadi Gull (`, 2025)
This paper discusses the multi-plicity of language utilized on signs in the public domain, on billboards, and in commercials, especially, how linguistic options indicate social identity, power relationships, and cultural hybridity within the post-urban and semi-urban environments. In a multicultural society such like Pakistan where the English, Urdu and Regional languages coexist, the language spoken in the public places acts as a symbolic depiction of the values with the society, classes and even the consumerism. This study investigates the selection of language used in a mixture of methods that utilize both visual interpretation and field observations of signs, advertisements, and other forms of communications as well as the overall impact these decisions have on perception of the audience and overall accessibility. English is found to be favourably utilised in certain instances as a symbol of modernity and prestige whereas Urdu and local languages confirm localization messages in a bid to make them relatable. The research adds to the expanding body of literature regarding linguistic landscape documentation and asks critical questions concerning language tampering, inclusiveness, and representation of culture in mass media. It further reveals how commercial parties influence linguistic taste and collective minds by way of strategic language use. Keywords: Linguistic landscape, billboards, urban public signage, multilingualism and language policy, commercial advertising, English in Pakistan, Sociolinguistics, urban communication, the symbolic power.